Educating on spatial skills using a paper-folding-and-punched-hole videogame: gameplay data analysis - Garcia-Segarra, Pablo; Santamarta, Vicent; Falomir, Zoe (Frontiers in Education, 2024)
Paper folding and punched hole tests are used to measure spatial abilities in humans. These abilities are relevant since they are associated with success in STEM (Science, Technology, Engineering, Mathematics). This paper addresses the challenge of teaching spatial reasoning skills using an educational videogame, the Paper Folding Reasoning Game.The Paper Folding Reasoning Game is an interactive game which presents activities intended to help users train and understand how to fold a paper to get a specific shape (Part I), and the consequence of punching a hole on a folded paper (Part II). This educational videogame can automatically generate paper-folding-and-punched-hole questions with varying degrees of difficulty depending on the number of folds and holes made, thus producing additional levels for training due to its embedded reasoning mechanisms (Part III).This manuscript presents the results of analysing the gameplay data gathered by the Paper Folding Reasoning Game in its three parts. For Part I and II, the data provided by 225 anonymous unique players is analysed. For Part III (Mastermode), the data obtained from 894 gameplays by 311 anonymous unique players is analysed.In our analysis, we found out a significant difference in performance regarding the players who trained (i.e. played Part I and II) before playing the Mastermode (Part III) versus the group of players who did not train. We also found a significant difference in players' performance who used the visual help (i.e. re-watch the animated sequence of paper folds) versus the group of players who did not use it. Thus confirming the effectiveness of the Paper Folding Reasoning Game to train paper-folding-and-punched-hole reasoning skills. Statistically significant gender differences in performance were also found.